2017
DOI: 10.1200/jgo.2016.005314
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Hodgkin Lymphoma Treated at Cancer Institute, Chennai, India: Long-Term Outcome

Abstract: PurposePediatric Hodgkin lymphoma (HL) is a highly curable malignancy. Outcomes for pediatric HL may vary between developed and developing countries for multiple reasons. This study was conducted to ascertain the outcomes of children with HL at our center and to identify risk factors for recurrent disease.MethodsWe analyzed the outcomes of 172 consecutive, previously untreated patients with pediatric HL presenting at our center from 2001 to 2010. Patients were treated with either adriamycin, bleomycin, vinblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
1
20
0
1
Order By: Relevance
“…ABVD and COPP-ABV continue to be used as common chemotherapy regimens in pediatric HL. 7 , 30 The question of whether one can use interim PET response to eliminate RT in children treated with these regimens can only be answered by pediatric trials conducted on the basis of the same chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ABVD and COPP-ABV continue to be used as common chemotherapy regimens in pediatric HL. 7 , 30 The question of whether one can use interim PET response to eliminate RT in children treated with these regimens can only be answered by pediatric trials conducted on the basis of the same chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Our treatment guidelines recommend RT in all patients with bulky disease at presentation. 7 Following the availability of PET for interim response assessment, we considered the elimination of RT in patients with excellent metabolic response on interim PET, on a case-by-case basis. Despite treating a large proportion of our patients without RT, the EFS and OS were satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Childhood cancer care is only available at the tertiary level and since most functioning cancer centres are located in metropolitan cities, the rural sector remains deprived of this service [ 4 ]. This contributes to a delay in presentation where for example, it was found that 80% of children with neuroblastoma [ 5 ] and 40–60% of children with Hodgkin lymphoma [ 6 , 7 ] presented in advanced stages at treating hospitals.…”
Section: Introductionmentioning
confidence: 99%